AN IMPROVED SELECTION TECHNIQUE FOR FAST PACKET ROUTING IN COMPUTER NETWORK - Akinwale, A.T.; Adebayo, A.A.; Folorunso, O.; Adebayo, G.A. (International Journal of Computing, 2011)
Contention Awareness Input Selection (CAIS) technique was recently compared with traditional input selection techniques such as First Come First Serve (FCFS) and Round Robin (RR) as a way of improving routing techniques and proved to outperform the two techniques but not widely accepted because of packet starvation problem. In this paper, Contention-Age Input Selection (CAGIS) technique was designed to correct the shortcoming of CAIS. CAIS was modified by including flattening algorithm, treap and queueing theory to improve packet access and control contention age level in the input buffer. The design involved three phases of setting up the network topology using the network objects, initiating of an event scheduler and traffic sources to start/stop transmitting packet through the event scheduler which was implemented using object-oriented tool commands language of script simulation program. The paper concluded that whilst deterministic XY routing scheme and the adaptive Odd-Even routing algorithm were used with CAGIS and CAIS to compare their performance, it was observed that CAGIS performed better under the three synthetic traffic patterns of uniform, transpose and hotspot. The results has improved significantly on contention age level of packets in the input buffer by uniformly distributing them to output ports.